(untitled) (Damascus University Journal of arts and humanities sciences, 2022)
The research studies the belonging of the Akkadian, Ugaritic and Arabic languages ​​to a group of one origin, represented in a mother language that combines it with the rest of its sisters from the ancient oriental tongues such as Eblaite, Canaanite, and Aramaic with its dialects and branches, and other languages ​​that have been used in the ancient Near East since ancient times, and some of them are still used to this day. The great similarity and clear convergence between these languages ​​caught my eye with the participation of most of these languages ​​in the (Š stem), that proved in the Akkadian and Ugaritic languages, without Arabic. The idea of ​​the research was based on an attempt to prove the existence of more (Š stem) in the Arabic language, based on some evidence contained in the Arabic dictionaries.